Settlements' hierarchy and centrality in Bantul District Special Province of Yogyakarta, Indonesia - Henk Huisman; Wim Staffers (Faculty of Geography, Universitas Gadjah Mada, 1991)
In this article, the assessment of centrality of settlements in a district in Central Java is discussed This with a view to determine a system of service centres in the area which is functional for regional planning purposes. The study area, Bantu! District, is a densely populated area which boasts a large variety of services. The assumption is tested that both the geographical location of the district, close to the city of Yogyakarta, and the high mobility of the population, due to a well-developed public transportation system, allow for a situation whereby the hierarchical position of a settlement, based on the combination of services provided is not necessarily similar to the centrality of that very settlement, based on the number of incoming interactions. From an analysis of an intensive set of primary data, it shows that although the level in the hierarchy of a settlement largely coincides with its centrality level, the centrality level of some settlements considerably deviates from what might be expected on basis of these centres' service level.